Effect of Few-Layered Graphene on the Corrosion Behaviour of the Al-Cu Matrix Composites - Kaykilarli, Cantekin; Eken, Taha Yasin; Kucukelyas, Burak; Uzunsoy, Deniz (Springer, 2025)
In the transportation, maritime and aviation industries, aluminum alloys - particularly those in the 2xxx series (Al-Cu type) - are frequently used because they offer an ideal combination of properties, including toughness, a high strength-to-weight ratio and fatigue resistance. Graphene, a two-dimensional material with a single-atom thickness composed of carbon atoms arranged in a hexagonal lattice, attracts interest due to its remarkable properties and is commonly utilized as a reinforcement in composite materials. Few-layered graphene (FLG) reinforced Al-4 wt.% Cu matrix composites were prepared via mechanical alloying (MA, 500 rpm, ball-to-powder ratio 7 : 1), uniaxial pressing (300 MPa), and conventional sintering (59 degrees C, 3 hours, argon gas flow). The present work investigates corrosion behaviors of FLG (0.25 and 0.5 wt.%) reinforced Al-4 wt.% Cu composites with different MA durations. Open-circuit potential (OCP), potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS) measurements were carried out in a 3.5% NaCl solution to determine the corrosion behavior. Following the corrosion test, X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) analysis were performed on the specimen that exhibited the optimum results. The data obtained before and after the test were compared to investigate the structural changes that occurred as a result of the corrosion test. The analysis demonstrated that the sample reinforced with 0.5 wt.% FLG and subjected to 7 hours of MA had the highest corrosion resistance.
Keywords: aluminum; copper; metal matrix composites; graphene; corrosion; electrochemical impedance spectroscopy